Fe3GeTe2: a site-differentiated Hund metal - Taek Jung Kim; Siheon Ryee; Myung Joon Han (npj Computational Materials, 2022)
Abstract Magnetism in two-dimensional (2D) van der Waals (vdW) materials has lately attracted considerable attention from the point of view of both fundamental science and device applications. Obviously, establishing a detailed and solid understanding of their magnetism is the key first step toward various applications. Although Fe3GeTe2 is a representative ferromagnetic (FM) metal in this family, many aspects of its magnetic and electronic behaviors still remain elusive. Here, we report our new finding that Fe3GeTe2 is a special type of correlated metal known as “Hund metal”. Furthermore, we demonstrate that Hund metallicity in this material is quite unique by exhibiting remarkable site dependence of Hund correlation strength, hereby dubbed “site-differentiated Hund metal”. Within this new picture, many of the previous experiments can be clearly understood, including the ones that were seemingly contradictory to one another.